2020
DOI: 10.1088/1757-899x/821/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy feed forward neural network (FFFNN) model for the Jakarta Islamic index (JII) forecasting

Abstract: Feed Forward Neural Network (FFNN) model is the best model to forecast the time series data. In this research, The Fuzzy Feed Forward Neural Network (FFFNN) with backward propagation method is used to predict the Jakarta Islamic Index (JII) data time series in 2018. Fuzzy is used as input to the FFNN model because it is overcome the weaknesses of the inaccurate results of the FFNN when the data is unclear or incomplete. The purposes of this research are to explain the procedure to generate the FFFNN model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In addition, this study accomplishes that using small data of symmetric volatility information is better than using big data sample, this result indicates that small data of symmetric volatility information is full of high-quality information for better prediction accuracy, therefore, this result is consistent with Yudelson et al (2014) and Faraway and Augustin (2018) when they demonstrated that small data outperforms big data in prediction accuracy when small data generate superior inferences than the low-quality large sample. In conclusion, this paper supports the findings of Das et al (2017), Wibowo et al (2017), Alkhoshi and Belkasim (2018), Livieris et al (2019), Aslam et al (2020), Peng and Tang (2020), Wang et al (2020), Irsalinda et al (2020), Yu and Yan (2020), Gandhmal and Kumar (2020), and Peng and Tang (2020), in which modern techniques like machine learning, artificial intelligence and DL are effective tools in the capital markets by affording advanced knowledge to the financial investors for the well-organized managing of portfolios, to reduce trading risk and to make right financial decisions, which leads to the inevitability of using new technological techniques in Islamic capital markets due to the effectiveness of those modern techniques in the predicting process than other classical statistical tools which remained paralyzed to evaluate big data time series, this inevitability of updating the classical statistical tools obliges the financial investors and decision-makers to employ new techniques which only machine learning, artificial intelligence and DL can offer.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, this study accomplishes that using small data of symmetric volatility information is better than using big data sample, this result indicates that small data of symmetric volatility information is full of high-quality information for better prediction accuracy, therefore, this result is consistent with Yudelson et al (2014) and Faraway and Augustin (2018) when they demonstrated that small data outperforms big data in prediction accuracy when small data generate superior inferences than the low-quality large sample. In conclusion, this paper supports the findings of Das et al (2017), Wibowo et al (2017), Alkhoshi and Belkasim (2018), Livieris et al (2019), Aslam et al (2020), Peng and Tang (2020), Wang et al (2020), Irsalinda et al (2020), Yu and Yan (2020), Gandhmal and Kumar (2020), and Peng and Tang (2020), in which modern techniques like machine learning, artificial intelligence and DL are effective tools in the capital markets by affording advanced knowledge to the financial investors for the well-organized managing of portfolios, to reduce trading risk and to make right financial decisions, which leads to the inevitability of using new technological techniques in Islamic capital markets due to the effectiveness of those modern techniques in the predicting process than other classical statistical tools which remained paralyzed to evaluate big data time series, this inevitability of updating the classical statistical tools obliges the financial investors and decision-makers to employ new techniques which only machine learning, artificial intelligence and DL can offer.…”
Section: Discussionsupporting
confidence: 91%
“…One of the newest studies that applied ANNs in Islamic capital markets, a study by Aslam et al (2020), predicted that daily closing prices of the Islamic securities (KMI-30) index using ANNs, their results showed that ANNs provided high accuracy in the prediction process. Correspondingly, Irsalinda et al (2020) predicted the JKII using the neural networks based on the fuzzy feed-forward method, their results showed that the predicted model produced high prediction ability in reducing the error rate in the training and testing process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations